PENGARUH RISK BASED CAPITAL, PREMIUM GROWTH RATIO, DAN BEBAN KLAIM TERHADAP PROFITABILITAS PADA ASURANSI JIWA SYARIAH - Anita Anita; Rohmawati Kusumaningtias (ITB AAS Indonesia Surakarta, 2024)
This study aims to examine and analyze the effect of risk based capital, premium growth ratio, and claims expense on the level of profitability proxied by return on assets with research subjects Sharia life insurance companies in Indonesia. This study uses a quantitative research method with purposive sampling technique, which produces a sample of 17 sharia life insurance companies (consisting of 85 data) that are actively registered with the Indonesian Financial Services Authority in the 2016-2020 period. This study shows that the premium growth ratio and claim expense have no effect on the level of profitability. Meanwhile, risk based capital has an influence on the level of profitability